Peningkatan Manfaat CSR Melalui PKBL BUMN terhadap Perguruan Tinggi di Jawa Timur - Diana Sulianti (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2010)
Corporate Social Responsibility (CSR) is about businesses and other organizations going beyond the legal obligations to manage the impact they have on the environment and society. In particular, this could include how organizations interact with their employees, suppliers, customers and the communities in which they operate, as well as the extent they attempt to protect the environment. CSR broadly represents the relationship between a company and the wider communiry within which the company operates. It is recognition on the part of the business that 'for profit' entities do not exist in a vacuum, and that a large part of any success they enjoy is as much due to the context in which they operate as factors internal to the company alone. This article is describe the contribution of CSR resulted by The Stale Owned Company (BUMN) which head office was in East Java. Today, BUMN's CSR program in East Java has still concern in partnership and community development program. There are many colleges in East Java that can be involved by BUMN in order to advance the company. Colleges can be involved in case of research connection with necessity.